Inverse Scattering of a Dielectric Sphere Partially Buried in a Ground Plane Using a Radial Basis Function Network - Loo, C.; Hamid, M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An analytic solution of the problem of electromagnetic scattering by a dielectric spherical scatterer resting on, or partially buried in, an infinite perfectly conducting ground plane is approximated by partially truncated sphere and is formulated using the method of images. The scattered field coefficients are solved exactly so that the scattered field can be evaluated everywhere. In particular, the scattering cross section can be calculated as a function of the sphere radius and permittivity as well as the truncated sphere distance for any specified angle of incidence. The solution of this problem is relevant to analyze the scattering by complex threedimensional bodies, plastic mines, icebergs, rough surfaces, etc., in which the flat background can be modeled by the ground plane while the complex body can be simulated by a sphere or a system of spheres partially truncated and resting on the ground plane. In order to solve the inverse scattering problem, we employ a radial basis function network to take the scattered field complex coefficients for the TE and TM polarization case as the network inputs to predict the three outputs of the electrical radius, burial distance, and relative permittivity of the sphere. The trained network is able to retrieve the three aforementioned parameters from new data which is different from the learning data.